Actual problems and proposals concerning development of national system of design and ergonomics - Бугайов, В. І. (Proceedings of National Aviation University, 1998)
Considered are the most urgent problems of development of national system of design and ergonomics, their importance for spiritual, economic, social and cultural resurrection beginning from the educational system and its content, retraining, creation of corresponding center and including methods of design projection and development of design industry